Genomic methods for tracking bacterial pathogens for clinical and public health benefit: the need for genomic surveillance - Maiden, Martin C.J.; Rodrigues, Charlene M. C. (Henry Stewart Talks, 2022)
Genomic surveillance, How do we track pathogens?, Challenges in pathogen surveillance, Molecular techniques used in pathogen surveillance, Pitfalls in adopting sequence-based technologies